Arcade at the intersection of Homji Street and Horniman Circle - Ghosh, Ayan (2023)
Keystone over the arcade at the intersection of Homji Street and Horniman Circle. Homji Street is named after Behramji Homji (died about 1750), a wealthy Parsi merchant, who with his brother Nusserwanji (died about 1756), founded the fabulously wealthy Dadyseth business family. Homji and his descendants were long-time residents on this street.